PARENTING STYLES AND THEIR IMPACT ON COGNITIVE AND BEHAVIORAL DEVELOPMENT IN EARLY ADOLESCENCE - Irene Florensia Situmeang; Hasanuddin Manurung; Ayu Safira (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Early adolescence is a critical developmental stage characterized by rapid cognitive growth and heightened behavioral adjustment, during which parenting practices play a central role. Parenting styles have been widely associated with adolescent outcomes, yet evidence remains fragmented regarding their combined influence on cognitive and behavioral development during early adolescence. This study aims to examine the impact of different parenting styles on cognitive and behavioral development among early adolescents. A quantitative correlational design was employed involving adolescents aged 11–14 years and their parents, selected from multiple middle schools. Data were collected using validated parenting style questionnaires, standardized cognitive assessments, and behavioral rating scales completed by parents and teachers. Descriptive statistics, correlation analysis, and analysis of variance were applied to examine developmental differences across parenting styles. The results indicate that authoritative parenting is significantly associated with higher cognitive functioning and more adaptive behavioral regulation, while authoritarian and neglectful parenting are linked to lower developmental outcomes. Permissive parenting shows moderate but less consistent effects. The findings suggest that balanced parental responsiveness and control are essential for supporting healthy cognitive and behavioral development during early adolescence. Strengthening authoritative parenting practices may contribute to improved adolescent adjustment and inform family-focused educational and mental health interventions.